Praktyczne możliwości i problemy wykorzystania dźwigni operacyjnej - Dresler, Zbigniew (Practical Aspects of Using Operating Leverage, 2007)
Operating leverage is an important element of economic knowledge, especially in the fields of: financial management, managerial accounting, financial analysis, and business economics, etc. Therefore, definitions of operating leverage are given in almost every textbook on these subjects. However, in the majority of textbooks it has not been given much attention, especially, the potential to use the operating leverage in financial management of the firm. Similarly, financial literature neglects to discuss the practical aspects of using operating leverage in financial analysis and in the process oi establishing financial strategy of the firm. Consequently, the purpose of this paper is to improve the1 knowledge about the benefits and problems of practical use of this financial device.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 86-94